Transcription of single base oligonucleotides by ribonucleic acid-directed deoxyribonucleic acid polymerase. - Falvey, A K (1976)
The synthesis of DNA products complementary to artificial templates by the enzyme RNA-directed DNA polymerase isolated from avian myeloblastosis virus has been studied. Of the single base polyribonucleotides, poly (rC), poly(rA), and poly(rI) were active while poly (rG) and poly (rU) were almost inactive. The minimum length showing activity for an oligo (rC) template was 9; the minimum primer length of oligo(dG) was 3 or 4. In order to examine the fidelity of transcription, single base oligoribonucleotides of defined length were studied. Using (rC)13 as template and (dG)8as primer, the oligo (dG) product coelectrophoresed with the template. However, using (rA)-20 as template and (dT)10 as primer, a large (10-16s) product was formed. Similarly, using oligo (rI) (2.5S) as template and (dC)10 as primer, a large (greater than 22s) product was formed. No significant activity was obtained with oligo (rU) templates. RNA-directed DNA polymerase transcribes the various oligonucleotides differently: slippage with oligo (rA) and oligo (rI), faithful transcription with oligo (rC), and poor transcription with oligo (rU).